CRIMINALISTICS - SOURCE OF CRIME PREVENTION - SADÎC, Zafer (International Journal of Legal and Social Order, 2022)
The article addresses the role that the science of Forensics (Criminalistics) has in the prevention of crime, through the specific analysis of the elements that give it the character of a source of prevention, with reference to its object of study, and in the end, brief conclusions are expressed regarding the impact they have had and have the data obtained from forensic investigations in preventing and combating the phenomenon of criminality, as well as proposals for law ferenda to increase the contribution of information acquired in criminal investigations among the means of prevention.